The Merchant of Havana : The Jew in the Cuban Abolitionist Archive - Silverstein, Stephen, 1978- (Book collections on Project MUSE., 2016)
"As Cuba industrialized in the nineteenth century, two ideological forces appeared: anti-Semitism and abolitionism. As the antislavery movement became organized in Cuba, the argument grew that Jews participated in the African slave trade and in New World slavery, and that this participation gave Jews extraordinary influence in the new Cuban economy and culture. Because of the decidedly small Jewish population on the island in this era, this form of anti-Semitism sprang almost exclusively from mythological beliefs"--